Author development of training device for micro-basketball the «Clever ring» as mean of integral psychomotor development of children of 2-5 years old. - Lakhno E.G; Kozina Zh.L; Jagiello Marina (Kharkov National Pedagogical University, 2012)
A technical device is developed for micro-basketball for integral development of children 1-5 years. In research took part 52 children of age-dependent group of 1-2 years, 56 children of 3-4 years, 56 children, 4-5 years. It is suggested to execute throws in a basket from different distance and under a different corner. Also to give up the balls of different color and size in accordance with a color and size of basket from the set initial position. It is marked that exercises with a ball develop an orientation in space, regulate force and exactness of throw, develop measurement with naked an eye, adroitness, speed of reaction; normalize a volitional sphere emotionally. It is set that application of methods with the use of technical device is instrumental in the increase of indexes of physical preparedness and psychophysiological possibilities of children.